2014
DOI: 10.5489/cuaj.2049
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of complete penile duplication accompanied by multiple anomalies

Abstract: Diphallus (penile duplication) is very rare and seen once every 5.5 million births. It can be isolated, but is usually accompanied by other congenital anomalies. Previous studies have reported many concurrent anomalies, such as bladder extrophy, cloacal extrophy, duplicated bladder, scrotal abnormalities, hypospadias, separated symphysis pubis, intestinal anomalies and imperforate anus; no penile duplication case accompanied by omphalocele has been reported. We present the surgical management of a patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The various genital abnormalities seen in males were small penis and epispadias, abnormal or absent scrotum, and cryptorchidism in 80, 60, and 60% cases in the series by Keppler-Noreuil (2001), but diphallus has not been reported in these series. Moreover, Karaca (2014) has reported a case as the first one of complete penile duplication with omphalocele.…”
Section: Discussionmentioning
confidence: 96%
“…The various genital abnormalities seen in males were small penis and epispadias, abnormal or absent scrotum, and cryptorchidism in 80, 60, and 60% cases in the series by Keppler-Noreuil (2001), but diphallus has not been reported in these series. Moreover, Karaca (2014) has reported a case as the first one of complete penile duplication with omphalocele.…”
Section: Discussionmentioning
confidence: 96%
“…Due to wide variability in presentation the management strategies differ [ [5] , [6] , [7] , 9 ]. Surgical correction is individualized with the aim of achieving proper urinary continence and erection with adequate cosmesis [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to low incidence and varied presentation, not much is known about the underlying pathophysiology, management options and outcomes [ 2 , [5] , [6] , [7] ]. Here, we report a case of diphallia with associated penoscrotal transposition of 2 hemiscrotums.…”
Section: Introductionmentioning
confidence: 99%
“…True diphallia is the less common variety and usually presents with a wider range of associated malformations such as bladder and urethral duplication, exstrophy vesica, renal anomalies, bifid scrotum, anorectal malformations, bowel duplication, and vertebral anomalies ( 8 , 9 ). Bifid phallus is usually associated with less severe malformations ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Penile duplication and multiple associated anomalies can be managed with multiple surgeries (treatment of the associated anomalies and genital reconstruction) ( 9 ). De Oliveira et al ( 2 ) reported an isolated true partial diphallia that was managed in a single surgery with right penectomy and end-to-side anastomosis between the right urethra and the remaining urethra.…”
Section: Discussionmentioning
confidence: 99%